National cross sectional study of views on sexual violence and risk of HIV infection and AIDS among South African school pupils. Issue 7472 (14th October 2004) - Andersson, Neil; Ho-Foster, Ari; Matthis, Judith; Marokoane, Nobantu; Mashiane, Vincent; Mhatre, Sharmila; Mitchell, Steve; Mokoena, Tamara; Monasta, Lorenzo; Ngxowa, Ncumisa; Salcedo, Manuel Pascual; Sonnekus, Heidi
Abstract: Objective To investigate the views of school pupils on sexual violence and on the risk of HIV infection and AIDS and their experiences of sexual violence. Design National cross sectional study. Setting 5162 classes in 1418 South African schools. Participants 269 705 school pupils aged 10-19 years in grades 6-11. Main outcome measure Answers to questions about sexual violence and about the risk of HIV infection and AIDS. Results Misconceptions about sexual violence were common among both sexes, but more females held views that would put them at high risk of HIV infection. One third of the respondents thought they might be HIV positive. This was associated with misconceptions about sexual violence and about the risk of HIV infection and AIDS. Around 11% of males and 4% of females claimed to have forced someone else to have sex; 66% of these males and 71% of these females had themselves been forced to have sex. A history of forced sex was a powerful determinant of views on sexual violence and risk of HIV infection. Conclusions The views of South African youth on sexual violence and on the risk of HIV infection and AIDS were compatible with acceptance of sexual coercion and "adaptive" attitudes to survival in a violent society. Views differed little between the sexes.